Echocardiographic and clinical outcomes following beating heart NeoChord DS1000 mitral valve repair: a single centre case series - Brown, Amy; Jefferson, Hallie L.; Fatehi Hassanabad, Ali; Noss, Christopher; Webb, Nicole; Fedak, Paul W. M.; Kent, William D. T.; Adams, Corey (Frontiers in Cardiovascular Medicine, 2023)
Background: The NeoChord DS1000 system implants artificial neochords transapically, through a left mini-thoracotomy to treat degenerative mitral valve regurgitation (MR). Performed without cardiopulmonary bypass, neochord implantation and length adjustment is guided by transesophageal echocardiography. We describe imaging and clinical outcomes for a single center case series using this innovative device platform. Methods: In this prospective series, all study patients had degenerative MR and were considered for conventional mitral valve surgery. Moderate to high-risk candidates were screened for NeoChord DS1000 eligibility based on echocardiographic criteria. Study criteria included isolated posterior leaflet prolapse, leaflet-to-annulus index greater than 1.2, and coaptation length index greater than 5 mm. Patients with bileaflet prolapse, mitral annular calcification, and ischemic MR were excluded from our early experience. Results: Ten patients underwent the procedure, including 6 males and 4 females, with a mean age of 76±9.5 years. All patients had severe chronic MR and normal left ventricular function. One patient required conversion to an open procedure for failure to deploy neochords with the device transapically. The median number of NeoChord sets was 3 (IQR 2.3-3.8) . Immediate post-procedure (POD#0) degree of MR on echocardiography ranged from mild or less, and on postoperative day 1 (POD#1) from moderate or less. Average length of coaptation was 0.85±0.21cm and average depth of coaptation was 0.72±0.15cm. At 1-month follow-up echocardiography, MR was graded from trivial to moderate and left ventricular inner diameter dimensions decreased from an average of 5.4±0.4cm to 4.6±0.3cm. None of the patients who had successful NeoChord implantation required blood products. There was 1 perioperative stroke with no residual deficits. There were no device-related complications or serious adverse events. The median length of hospital stay was 3 (IQR 2.3-10) days. 30-day and 6-weeks postoperative mortality and readmission rates were 0%. Conclusion: We report the first Canadian case series using the NeoChord DS1000 system for off-pump, transapical, beating heart mitral valve repair, through a left mini-thoracotomy. The early surgical outcomes suggest this approach is feasible, safe, and effective in reducing MR. This novel procedure has the advantage of offering a minimally invasive, off-pump option for select patients with high surgical risk.